The economies of Southeast Asia : the growth and development of ASEAN economies - Tongzon, Jose L., 1951- (Cheltenham, UK ; Northampton, MA, USA : E. Elgar, 1998)
The Economies of Southeast Asia provides a modern, authoritative introduction to the economic development of the Association of Southeast Asian Nations (ASEAN). It evaluates the extent to which the phenomenal growth in the region is due to ASEAN cooperation. This comprehensive book includes an examination of the latest research on ASEAN growth and development. It will be an ideal main text for courses on Asian economics, development economics, development studies and comparative economic systems in both the East and West.
Pt. 1. ASEAN Economic Development and Cooperation. 1. Evolution of ASEAN cooperation and institutional structure. 2. ASEAN economic development: an overview. 3. ASEAN development and economic cooperation. 4. Sub-regional economic cooperation. 5. The role of government in ASEAN -- Pt. 2. ASEAN External Economic Relations. 6. ASEAN economic relations: the US, Japan, the EU, China and Vietnam. 7. ASEAN and other regional trading arrangements. 8. Regionalism, multilateralism and the World Trade Organization. 9. Role of foreign direct investment (FDI) in ASEAN -- Pt. 3. Future ASEAN Economic Cooperation and Challenges. 10. ASEAN economic cooperation under AFTA. 11. ASEAN free trade area and the newly emerging Southeast Asian economies. 12. Economic interdependence in ASEAN. 13. Domestic capital development and the environment.
Includes bibliographical references (p. 223-242) and index.
Keywords: Southeast Asia -- Economic conditions; Southeast Asia -- Economic integration